Pembelajaran Via Google Classroom sebagai Alternatif Solusi Efektif Pembelajaran di Era Pandemi - Robiatul Munajah; Rizqon Halal Syah Aji (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This study tries to illustrate how students can access alternative learning techniques via online ways during a pandemic. In the Covid-19 emergency, educators and students will have a unique experience. The government implemented a policy on online education to enable pupils to learn even when they are socially isolated. The impact of the learning process throughout the epidemic since the start of 2020 is the result of digital transformation efforts as a means of instruction for teachers and pupils. This research employs a descriptive qualitative approach. The primary sources of data are teachers and students in elementary schools. Data collecting strategies included observation, interviewing, and documenting learning activities using Google Classroom during the COVID-19 epidemic. The results indicated that around 80% of the time spent using google classroom in the student learning process during the online learning period was due to the fact that it was more effective and efficient than using zoom or google meet. This demonstrates that teachers may give online learning solutions by leveraging a variety of online platforms, one of which is a Google product called Google Classroom.Keywords: Google Classroom; Online Learning; Pandemic; Social Distancing; Digital Transformation AbstrakPenelitian ini mempunyai tujuan untuk menjelaskan langkah alternatif pembelajaran terhadap peserta didik melalui metode online di masa pandemi. Pengalaman berbeda bagi pendidik maupun siswa pada keadaan darurat Covid-19. Pemerintah mengeluarkan kebijakan tentang pembelajaran via online difungsikan agar siswa dapat belajar meski dalam keadaan social distancing. Upaya transformasi digital sebagai metode pembelajaran bagi guru dan siswa merupakan dampak dari proses pembelajaran selama pandemi sejak awal tahun 2020. Metode penelitian pada riset ini adalah penelitian kualitatif dengan jenis deskriptif. Sumber data berasal dari para guru dan para siswa di sekolah dasar. Pengumpulan data dilakukan dengan tehnik observasi, wawancara dan dokumentasi dengan instrumen lembar wawancara serta catatan lapangan mengenai kegiatan pembelajaran selama pandemi covid-19 dengan menggunakan google classroom. Hasil penelitian menunjukkan 80% penggunaan google classroom dalam proses belajar siswa pada masa pembelajaran online lebih banyak digunakan dengan alasan penggunaan kuota internet dan waktu yang lebih efektif dan efisien, dibandingkan dengan menggunakan zoom atau google meet. Hal tersebut secara signifikan menunjukkan bahwa guru dapat memberikan solusi untuk pembelajaran online dengan memanfaatkan berbagai platform online salahsatunya produk google yaitu google classroom.Kata kunci: google classroom; pembelajaran online; pandemi; social distancing; transformasi digital